Efektifitas Bimbingan Kelompok dalam Meningkatkan Kepercayaan Diri Anak-Anak Panti Asuhan Aisyiyah Putri Kota Payakumbuh - Melandi Oktari; Syawaluddin Syawaluddin (Institut Teknologi dan Bisnis Semarang, 2024)
This research was taken based on the existence of children at the Aisyiyah Putri Orphanage in Payakumbuh City who had low self-confidence. This is due to the nature of being afraid to speak and express opinions in public, difficulty adapting to new environments and difficulty respecting other people's opinions. In fact, it is not uncommon for children in orphanages to doubt their own abilities and feel inferior to other people. Researchers tried to apply group guidance services to the children of the Aisyiyah Putri Orphanage in Payakunbuh City. This research aims to increase their self-confidence. The method used in this research is pre-experiment, one group pre-test, post-test. The subjects of this research were the children of the Aisyiyah Putri Orphanage in Payakumbuh City. The data analysis technique uses the Wilcoxon signed rank test. The instrument used in this research is a measurement scale in the form of a questionnaire. The results of this research can be seen from the implementation of the pre-test and post-test, namely that there is an increase in self-confidence in each child at the Orphanage. Wilcoxon signed rank test analysis shows a value of 0.018 which is lower than 0.05, so it can be concluded that there is an increase in self-confidence of the children of the Aisyiyah Putri Orphanage in Payakumbuh City through group guidance treatment at the Aisyiyah Putri Orphanage in Payakumbuh City.